Mutational Screening of Skeletal Genes in 14 Chinese Children with Osteogenesis Imperfecta Using Targeted Sequencing - Wei Tan; Yuelun Ji; Yuepeng Qian; Yongchang Lin; Ruolian Ye; Weiping Wu; Yibin Li; Yongjian Sun; Jianyin Pan (Journal of Immunology Research)
Background. As a heterogeneous hereditary connective tissue disorder, osteogenesis imperfecta (OI) is clinically characterized by increased fracture susceptibility. Analysis of genetic pathogenic variants in patients with OI provides a basis for genetic counseling and prenatal diagnosis. Methods. In this study, 14 diagnosed OI patients from sporadic Chinese families were enrolled to be screened for potential mutations from these patients by next-generation sequencing technology. Results. 34 different variants were identified. 18 variants were from 4 OI-related genes including COL1A1, COL1A2, P3H1, and WNT1, and 10 variants are novel. Most OI patients (11 out of 14, 78%) harbor variants in type I collagen genes. Conclusions. Our results support previously established estimates of the distribution and prevalence of OI mutations and highlight both phenotype and genetic heterogeneity among and within families. We report several novel variants of OI, which expands the clinical spectrum of OI. In summary, our data provides disease-causing genes information for genetic counseling towards OI patients and families and also provides a reference for clinicians in the diagnosis of OI, also in prenatal diagnosis of this disease.